ANALYSIS OF MAQASHID SHARIA AND FIQIH AL-BI'AH ON WASTE BANKS IN REALIZING GREEN ECONOMY IN BANTUL DISTRICT - Fitriana Annisa; Eko Priyojadmiko; Muhammad Arif Kurniawan (Journal of Global Business and Management Review, 2023)
ABSTRACT The purpose of this study is to determine the application of the principles of protecting religion (hifdzu din), protecting the soul (hifdzu nafs), protecting the intellect (hifdzu aql), protecting property (hifdzu mal), and protecting offspring (hifdzu nasab) in realizing the concept of Green Economy, as well as knowing the application of the principle of protecting the environment (hifdzu bi'ah) in realizing the concept of Green Economy at the Gemah Ripah Waste Bank Badegan Bantul. This type of research is qualitative research. The data sources used are human resources involved in the management of the Waste Bank. The data collection techniques of this research are participatory observation, in-depth interviews, and document studies. The analysis technique uses data reduction, data presentation, and conclusion drawing. The result of this research is that there is an application of the Maqashid Syariah principle in the management of the Waste Bank. The principle of preserving religion can be seen from the provisions of running worship time, praying before starting activities. The principle of preserving the soul is seen in the provision of complete work tools, health insurance for employees. The principle of preserving the mind is seen in the education of the community about protecting the environment, the benefits of the waste bank, the emergence of community creativity. The principle of protecting property is seen in the amount of wages for waste bank employees, recording every transaction by tellers, savings for customers. The principle of protecting offspring, seen from the existence of waste management does not violate religious norms, and health check programs. While the value of fiqih al-bi'ah or protecting the environment (hifdzu bi'ah) is realized by the waste management program, the counseling program and the emergence of pilot waste banks in each sub-district. The principles of Maqashid sharia and Fiqh al biah are a form of effort to improve the economy that still protects the environment and reduces the risk of environmental damage or ecological scarcity (Green economy).